THE REALITY OF AMERICAN NATION SLAVERY IN THE NOVEL INCIDENTS IN THE LIFE OF A SLAVE GIRL BY HARRIET ANN JACOBS - Abbas, Abbas (JURNAL ILMU BUDAYA, 2020)
This article discusses the social facts experienced by Americans in literature, especially novel. Literary work as a social documentation imagined by the author is a reflection of the values of a nation or ethnicity. The main objective of research is to trace the reality of slavery that occurred in America as a social fact in literary works. This research is useful in strengthening the sociological aspects of literary works as well as proving that literary works save a social reality at the time so that readers are able to judge literary works not merely as fiction, but also as social documentation. The writer in this study uses one of the literary research methods, namely Genetic Structuralism Approach. This method emphasizes three main aspects, namely literary work, the background of the author's life, and social reality. Novel Incidents In The Life Of A Slave Girl written by Harriet Ann Jacobs in 1858 was used as primary research data, then a number of references about the author's social background and the reality of slavery in the history of the American nation became secondary data. Primary and secondary research data obtained through literature study. Based on the results of this study found the events of slavery in the history of the American nation. Slavery was the act of white Americans forcibly employing black Negroes on the lands of plantation and agricultural also mining areas. Slavery is a valuable lesson for Americans in protecting human rights today as well as a historic lesson in building the American national spirit, namely freedom, independence, and democracy. The reality of slavery is reflected in the novel Incidents In The Life Of A Slave Girl as well as the life experience of its author, Harriet Ann Jacobs.